PENGARUH FAKTOR KEUANGAN DAN PEMASARAN TERHADAP KELAYAKAN USAHA PO. KERIPIK PISANG SUSENO DI BANDAR LAMPUNG - Yudiana Yudiana (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
The object of research is PO. Pisang Suseno Bandar Lampung Chips located at Jalan Ikan kakap No. 78 Teluk Betung. PO. The problem studied was to find out the influence of financial and marketing factors on business feasibility of PO. Suseno Banana Chips in Bandar Lampung because of the business feasibility of PO. Suseno Banana Chips in Bandar Lampung business feasibility PO. Suseno Banana Chips in Bandar Lampung are declining. The research method used in this study is library research carried out by reading and studying books, scientific works and other library support related to this research and field research conducted by examining directly on PO. Suseno chips in Bandar Lampung through interview methods and questionnaires related to financial and marketing factors to the business feasibility of Suseno Keripik in Bandar Lampung. The results showed that the influence of financial and marketing factors on business feasibility of PO. Suseno Chips in Bandar Lampung, Based on calculations and research results from several financial feasibility criteria, it can be seen that the Net Present Value (NPV) is 226,745,626 and the Profitability Index (PI) is 1.87, the Internal Rate of Return (IRR) is 40.47% and Payback period (PP) for 2 years 23 days. This business should be developed in the direction of a larger processing industry given the products of PO chips. Suseno is a product that is quite popular with the community and this business can be used as an example by various parties who want to pursue similar businesses.